Accelerated Fenton degradation of azo dye wastewater via a novel Z-scheme CoFeN-g-C3N4 heterojunction photocatalyst with excellent charge transfer under visible light irradiation. Issue 45 (31st October 2022) - Miao, Shihao; Gao, Hongcheng; Xia, Hongyu; Mao, Xiaoxia; Zhang, Lijuan; Shi, Mengqin; Zhang, Yuanguang
Abstract : A schematic illustration of the photo-Fenton degradation of azo dyes by a Z-scheme CFN-CN1 heterojunction under visible light irradiation. Abstract : A novel Z-scheme heterostructure photocatalyst, CoFeN-g-C3 N4 (CFN-CN), was prepared by a simple strategy, and its heterostructure and a photo-Fenton system were used to synergistically catalyze the degradation of azo dyes. The experimental results showed that the CFN-CN1 heterojunction exhibited superior photocatalytic degradation performance, and the degradation rate of Methyl Orange (MO) reached 96.8% in 40 min. The degradation rate constants were 11.8 and 2.81 times those of CN and CFN, respectively. CFN-CN1 also shows excellent catalytic degradation performance for other azo dyes (Congo Red (CR), Acid Orange 7 (AO7), Mordant Black 17 (MB17) and Acid Red B (ARB)), and the degradation efficiencies all exceeded 90%. Furthermore, the addition of inorganic anions (Cl −, HCO3 − and SO4 2− ) affects the degradation of azo dyes, especially HCO3 − which significantly promotes the degradation of MO. The radical trapping experiments and EPR results indicated that superoxide radicals (˙O2 − ) and hydroxyl radicals (˙OH) were the main active species. The above research reveals that the CFN-CN heterojunction synergistic photo-Fenton system may provide new hints for the degradation and removal of azo dyes from wastewater.